Effect of Auricular Acupressure on Acute Nausea and Vomiting Induced by Chemotherapy among Breast Cancer Patients - Mohammad Eghbali; Shokoh Varaei; Seyedeh Fatemeh Jalalinia; Mozhgan Aalam Samimi; Kiarash Sa'atchi; Mir Saeed Yekaninejad (Tehran University of Medical Sciences, 2015)
Background & Aim: Approximately 75% of patients with cancer experience acute nausea and vomiting (24 hours after chemotherapy). The aim of this study was to determine the effect of auricular acupressure in relieving acute nausea and vomiting among women with breast cancer receiving chemotherapy .   Methods & Materials: This study was a posttest only randomized clinical trial conducted on 48 women with breast cancer receiving chemotherapy in Imam Khomeini and Hazrat Rasoul Akram hospital. Before chemotherapy and after obtaining informed consent, the patients were randomly allocated into intervention and control groups. Intervention group received routine medications for controlling nausea and vomiting as well as auricular acupressure. Meanwhile, the control group received only the routine medications. The data were gathered using demographic and Morrow Standard questionnaire and were compared using statistical tests in the SPSS-21 .    Results: T he results showed that using auricular acupressure led to a decrease in the number and the intensity of nausea at acute phases (P=0.001). Acupressure application did not lead to any complications in the patients .   Conclusion: According to the results of this study, using auricular acupressure on Shenmen, Point zero, stomach, Brainstem, and cardia points can relieve nausea and vomiting at acute phase of chemotherapy. It is suggested that nurses use this pressure technique as a complementary treatment for relieving nausea and vomiting caused by chemotherapy.